Resilience of rainfed agriculture in northern part of Cyprus: a comprehensive drought severity level impact analysis and adaptive strategies - Payab, Ahmad Haseeb; Turker, Umut (Springer, 2025)
Like many other Mediterranean countries, rainfed agriculture in the northern part of Cyprus faces heightened vulnerability due to the escalating brunt of climate change, particularly the incidence of drought. Recent instances of drought have significantly curtailed crop yields within rainfed agriculture, amplifying economic concerns. Consequently, the authorities have been compelled to increase imports to maintain a balance between supply and demand. In this comprehensive research, the Reconnaissance Drought Index has been employed to meticulously figure out and evaluate drought occurrences across diverse regions of Cyprus spanning from 1977 to 2013. To gauge the ramifications of drought severity levels, the Crop Simulation Model (CROPWAT) was employed. This model enabled the assessment of how drought affects the yields of rainfed wheat, barley, and olive crops. The study's findings are unequivocal in underscoring the deleterious after-effects of drought on rainfed crop production. The reductions due to droughts in the production of olive, barley, and wheat were stark, with average reductions of 49%, 28%, and 37%, respectively. As severity levels escalate, yield reductions become notably more pronounced. For wheat, the average yield reduction at extreme drought conditions was 44%, reducing to 28% and 38% for moderate and severe drought severity levels, respectively. Similarly, barley displayed reductions of 19%, 29%, and 35%, while olive crops exhibited yield reductions of 45%, 48%, and 54%. Furthermore, the study divulges that soil attributes, primarily the water-holding capacity, wield substantial influence in constraining crop yields during drought episodes. The analysis attests to a linear reduction in yields as soil water storage dwindles. Through comparisons with other studies particularly in the Mediterranean region, we established global relevance. Notably, the study extended beyond analysis, proposing co-creation and digital transformation as innovative strategies to mitigate drought impacts and align with sustainable development goals. This research exemplifies interdisciplinary work, informing policy decisions and enhancing agricultural resilience against climate change.
Keywords: Rainfed agriculture; Drought; CROPWAT; RDI; Co-creation; Digital transformation